Producción secundaria de una población de Chione cancellata (Bivalvia: Veneridae) de la costa sur del Golfo de Cariaco, Venezuela - Prieto A, Antulio S (Universidad de Costa Rica, 1998)
Production and biomass of Chione cancellata, an abundant species in Thalassia testudinum sea beds, were studied from March, 1984 to May, 1985 in Guaracayal, Cariaco Gulf, Venezuela. The population distribution ranges were stable. Many individuals were 20-30 mm long (80%) and recruitment was low. The mean density was 45.54 ind m' with a mean standing dry weight biomass of 7.37 g m', both changed significantly with time. Growth rates in marked bivalves of different size classes was maximum in the period between 14-X- 1984 and 10-V-1985. A production of 17 .34 g m' year' was obtained using a method designed to study populations with continuous reproduction and indistinguishable age classes. The greatest production values were obtained for cockles 20 to 30 mm in length. Highest production was between 28-Il-1985 and 27-IV-1985. The annual tumover rate (PIB) was 2.65 year'.